2007
DOI: 10.1111/j.1467-9523.2007.00444.x
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctionality in Agriculture and its Agents: Regional Comparisons

Abstract: Drawing on a multidisciplinary survey carried out in three contrasting areas of the Rhône-Alpes Region in France, this article investigates how the concept of multifunctionality has been understood and appropriated. After a retrospective look at French agricultural policy, the first part presents our analytical framework, which is inspired by the sociology of action. The second part analyses the socio-political issues of farming in each area and the compromises established around the various functions attribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 4 publications
(4 reference statements)
0
21
0
3
Order By: Relevance
“…Given the risks we confront-the increasingly tangible nature of personal health and ecological risks (water quality, climate change, biodiversity)-and the search for new types of accountability mechanisms in the wake of widespread state and market failures, it would seem that there will be increasing demand for professionalization of agriculture (See Dufour et al 2007 for an analysis of professionalism in French agriculture). Additional opportunities for farmers to make claims and deliver added value in agrifood systems lie in animal rights, human rights (i.e., worker safety, immigration considerations) and integrity of artisanal or quality products.…”
Section: Professions As Collective Formsmentioning
confidence: 98%
“…Given the risks we confront-the increasingly tangible nature of personal health and ecological risks (water quality, climate change, biodiversity)-and the search for new types of accountability mechanisms in the wake of widespread state and market failures, it would seem that there will be increasing demand for professionalization of agriculture (See Dufour et al 2007 for an analysis of professionalism in French agriculture). Additional opportunities for farmers to make claims and deliver added value in agrifood systems lie in animal rights, human rights (i.e., worker safety, immigration considerations) and integrity of artisanal or quality products.…”
Section: Professions As Collective Formsmentioning
confidence: 98%
“…Fruto del vínculo difícilmente indisociable entre la disponibilidad hídrica y la actividad agrícola se han configurado unos paisajes resultantes de la mezcla entre la práctica ancestral del regadío tradicional y la apuesta por nuevos proyectos de riego en dominios de secano. Un marco donde conviven sistemas de riego tradicionales que después de un estado de (medio) abandono se ha modernizado con el fin de adaptarse a las demandas de carácter ambiental y afianzar con ello la multifuncionalidad del regadío desde su carácter patrimonial y/o lúdico (Dufour et al, 2007).…”
Section: De La Gestión Tradicional Del Regadío Al Enfoque Territorialunclassified
“…Pluriactivity refers to the involvement in off-farm paid employment by either the farm operator and /or spouse. Agriculture no longer derives its legitimacy solely from its economic role in producing raw agricultural materials, but also from the provision of landscape and ecosystem services, public goods and the production of social and cultural ties (Dufour et al, 2007 'traditional' agriculture in maintaining the considerable environmental and aesthetic assets of the European countryside, along with its social cohesion.…”
Section: Multifunctionalismmentioning
confidence: 99%
“…The lack of enthusiasm for multifunctional agriculture is not confined solely to the peripheral Iveragh. A comprehensive study undertaken in France by Dufour et al (2007), found that multifunctionlism had greatest support among researchers and agri-administrators, rather than among farmers on the ground, whose identity is still strongly linked with farming and producing a product, rather than selling a service or an image. Similarly, a recent study in Belgium found that only 5% of total income in the farming sector comes from diversified activity of which the major part is linked to agri-tourism and direct sales (Van Huylenbroeck, et al, 2007).…”
Section: Multifunctionalismmentioning
confidence: 99%